PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE BERBANTU MEDIA GASER TERHADAP KETRAMPILAN MENULIS DESKRIPSI SISWA KELAS IV SD N NGESREP 01 - Rahayu Astriani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This research was conducted in SD N Ngesrep 01, by examining the fourth grade children in the 2nd half 2016/2017 school year totaling 30 children. This research is a quantitative research. This study was conducted to determine the effect of non-teaching model example non example of media-assisted gaser the description writing skills of students. Data description writing skills of children are analyzed using observational methods. The data was then analyzed by statistical analysis methods. The result showed that there was the influence of the learning model example non example of media-assisted gaser the description writing skills of students. On learning model example non example media-assisted gaser media experience influence on description writing skills of fourth grade students who initially low into the high category.